2017
DOI: 10.1038/s41467-017-00647-9
|View full text |Cite
|
Sign up to set email alerts
|

Engineered factor Xa variants retain procoagulant activity independent of direct factor Xa inhibitors

Abstract: The absence of an adequate reversal strategy to prevent and stop potential life-threatening bleeding complications is a major drawback to the clinical use of the direct oral inhibitors of blood coagulation factor Xa. Here we show that specific modifications of the substrate-binding aromatic S4 subpocket within the factor Xa active site disrupt high-affinity engagement of the direct factor Xa inhibitors. These modifications either entail amino-acid substitution of S4 subsite residues Tyr99 and/or Phe174 (chymot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 62 publications
2
36
0
Order By: Relevance
“…In exploration of RIV rescuing agents, Verhoef et al. () found that the F174A mutant of FXa was resistant to the RIV‐like inhibitor, Apixaban, while retaining the catalytic activity, and suggested local modifications on S4 pocket may reduce the binding affinity of the direct inhibitor to FXa. However, Verhoef's computational simulations mainly focused on the mobility of the 99 loop in wild‐type and P. textilis isoform FXa, and did not elaborate the molecular mechanism of the F174A mutant in detail.…”
Section: Introductionmentioning
confidence: 99%
“…In exploration of RIV rescuing agents, Verhoef et al. () found that the F174A mutant of FXa was resistant to the RIV‐like inhibitor, Apixaban, while retaining the catalytic activity, and suggested local modifications on S4 pocket may reduce the binding affinity of the direct inhibitor to FXa. However, Verhoef's computational simulations mainly focused on the mobility of the 99 loop in wild‐type and P. textilis isoform FXa, and did not elaborate the molecular mechanism of the F174A mutant in detail.…”
Section: Introductionmentioning
confidence: 99%
“…The HEK cells were transfected with pcDNA‐FIX using the calcium phosphate coprecipitation method . To generate cell lines stably expressing FIX, individual clones were expanded and selected in media containing 450 μg/mL geneticin essentially as described previously for recombinant FX expression . In following, the stable HEK‐FIX cells were transiently transfected with pcDNA‐VKORC1.…”
Section: Methodsmentioning
confidence: 99%
“…15 To generate cell lines stably expressing FIX, individual clones were expanded and selected in media containing 450 μg/mL geneticin essentially as described previously for recombinant FX expression. 16 In following, the stable HEK-FIX cells were transiently transfected with pcDNA-VKORC1. Transfection with FIX and VKORC1 was confirmed by performing RT-PCR to demonstrate transcription of the transgene.…”
Section: Cell Culture and Transfection Of Recombinant Human Factor IXmentioning
confidence: 99%
“…65 Both venom proteins comprise exceptional structural and functional features, 66 with venom FXa carrying specific modifications of the substrate-binding aromatic S4 subpocket within its active site that disrupt high-affinity engagement of the direct FXa-inhibiting oral anticoagulants. 67 Human FX variants comprising a similarly modified S4 subsite resulting either from a single point mutation at position Phe174 (chymotrypsinogen numbering) or insertion of a unique snake venom FXa 99-loop demonstrated a 10-to 100-fold loss of FXa inhibitor-sensitivity. 67 As these FX variants are able to restore hemostasis in plasma inhibited by the FXa inhibitors, they have the potential to bypass the direct factor Xa inhibitor-mediated anticoagulation in patients that require restoration of blood coagulation.…”
Section: Risk Stratification Of Patients With Acute Pulmonary Embolismentioning
confidence: 99%
“…67 Human FX variants comprising a similarly modified S4 subsite resulting either from a single point mutation at position Phe174 (chymotrypsinogen numbering) or insertion of a unique snake venom FXa 99-loop demonstrated a 10-to 100-fold loss of FXa inhibitor-sensitivity. 67 As these FX variants are able to restore hemostasis in plasma inhibited by the FXa inhibitors, they have the potential to bypass the direct factor Xa inhibitor-mediated anticoagulation in patients that require restoration of blood coagulation. The gut microbiota is an environmental factor that impacts vascular physiology, locally in the intestine, 68 but also through remote signalling.…”
Section: Risk Stratification Of Patients With Acute Pulmonary Embolismentioning
confidence: 99%